The influence of competitive bidding on entrepreneurial orientation and business growth of quantity surveyors in South Africa - Diko, Sakhumzi (My University, 2018)
After the Competition Commission of South Africa condemned and put a stop to the mandatory use of government gazetted fee scales for Professional Quantity Surveyors (PrQS), competitive bidding was introduced as a procurement system for professional services. The South African quantity surveyors are now competing on bid price for contract appointments in the public sector (competitive bidding). Discounts offered have increased exponentially over the years, especially in periods of work scarcity. This study investigates the influence that competitive bidding has on business growth. Secondly, the study assesses how the entrepreneurial orientation of quantity surveying practices is influenced by competitive bidding. A review of relevant literature identified the challenges that are brought about by competitive bidding. The study also focused on entrepreneurial orientation and identified similarities between what is required for competitive bidding and what dimensions of entrepreneurial orientation a quantity surveyor should possess. The research methodology is quantitative in nature and the data collection method used is a web-based questionnaire which explored the three variables, competitive bidding, business growth and entrepreneurial orientation. The results suggest that quantity surveyors who possess entrepreneurial orientation are less influenced by competitive bidding and that competitive bidding does have a negative influence on business growth. Key findings made included that bid price alone should not be used to determine the suitability of a firm. Rather, the quality of work, experience and qualifications must form the basis of the criteria for determining a firm’s suitability. It is further recommended that the competition law be amended to exclude quantity surveying practices and other professional service providers from competitive bidding.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation
Keywords: Entrepreneurship; Entrepreneurship--South Africa; Organizational effectiveness--South Africa